1957
DOI: 10.1021/ja01562a041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Properties of Certain 5,6-Dichlorobenzimidazole Ribosides

Abstract: Certain 5,6-Dichlorobenzimidazole Ribosides 1185 Diehl for a supply of 2,3-O-benzylidene-d-D-ribofuranose and of 2,3,5-tri-O-benzoyl-D-ribose. Analyses were performed in the Institutes' Micro-analytical Laboratory under the supervision of Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1962
1962
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Reaction of the mercury salt of 5-amino-4-nitropyrazole and tribenzoylribfuranose chloride20 in heated toluene gave exclusively the 3-amino-4-nitropyrazole nucleoside.…”
Section: Resultsmentioning
confidence: 99%
“…Reaction of the mercury salt of 5-amino-4-nitropyrazole and tribenzoylribfuranose chloride20 in heated toluene gave exclusively the 3-amino-4-nitropyrazole nucleoside.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Raney nickel mediated dethiation of 5 furnished a compound with the same properties as those reported for DRB. 19 Previous reports of l-/?-D-ribofuranosylbenzimidazole nucleosides29-31 indicate that the Jy.%' coupling constants tend to be >5 Hz for such compounds and therefore cannot be used to establish anomeric configuration. We found that all nucleosides (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) prepared in this study possessed a Jy.% >5 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…19 Previous reports of l-/?-D-ribofuranosylbenzimidazole nucleosides29-31 indicate that the Jy.%' coupling constants tend to be >5 Hz for such compounds and therefore cannot be used to establish anomeric configuration. We found that all nucleosides (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) prepared in this study possessed a Jy.% >5 Hz. However, the dethiation of 5 to give DRB (with a Jy.y of 6.3 Hz) established the /3-anomeric configuration for all nucleosides (4-23).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations